Simulation of the Lumbar Spine as a Multi-Module Paralel Manipulator - M. Ceccarelli; R. C. Saltarelo; G. Carbone; J. C. M. Carvalho (Applied Bionics and Biomechanics)
In this paper a simulation of movements of lumbar spine is proposed by using a model with serially connected parallel manipulators. An analysis has been computed for the human spine structure and its movements, in order to simulate the motions and forces that actuate a spine specifically in the lumbar segment. A mechanical model has been designed with available identified parameters of human spine, by using characteristics of parallel manipulators and spring stiffness. This model is suitable to properly simulate the trunk behavior at macroscopic level but also the smooth behavior of intervertebral discs and actuating motions of muscles and tendons. Simulation results for spring actions and joints reaction forces can give an evaluation of the forces that intervertebral discs supports during motions of a real spine.